Ginsenoside Rb1 Interfered with Macrophage Activation by Activating PPARγ to Inhibit Insulin Resistance in Obesity - Hongyue Ding; Jinxiang Dong; Yuqi Wang; Qiang Huang; Jie Xu; Zhidong Qiu; Fan Yao (Molecules, 2023)
Type 2 diabetes (T2D) is characterized by insulin resistance (IR), often accompanied by inflammation. Macrophage activation acts as an inflammatory response, which is characterized by macrophage recruitment in the initial stage. Ginsenoside Rb1 (Rb1) is a main active ingredient, which is known for its fat-reducing, anti-inflammatory effects. To clarify that Rb1 regulates macrophage activation in adipose tissue and improves tissue inflammation, network pharmacology and molecular docking were used for target prediction and preliminary validation. By constructing the co-culture model of adipose-derived stem cells (ADSC) and primary macrophage (PM), the body adipose tissue microenvironment was simulated to observe the adipogenesis degree of adipocytes under the effect of Rb1. The levels of cytokines, macrophage polarization, and protein or RNA expression in the inflammatory signaling pathway were finally detected. The results showed that 89 common targets of T2D-Rb1 were obtained after their intersection. Furthermore, according to the results of the KEGG pathway and PPI analysis, PTGS2 (COX-2) is the downstream protein of PPARγ-NF-κB. The molecular binding energy of PPARγ-Rb1 is −6.8 kcal/mol. Rb1 significantly inhibited the increase in MCP-1, TNF-α, and IL-1β induced by hypertrophic adipocytes supernatant and promoted the expression of IL-10. Rb1 inhibited the activation of inflammatory macrophages and PM migration and upregulated PPARγ expression with the blocking of NF-κB activation. Additionally, Rb1 promoted the expression of IRS1 and PI3K in the insulin signal pathway, which had a similar effect with ROS. Therefore, Rb1 might affect macrophage activation through PPARγ, which might alleviate obese insulin resistance in T2D early stage.